Coarctation Balloon Angioplasty in A Four Months Old Infant Following End to End Coarctation Repair: A Case Report (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v33i2.5686Bangladesh Journal of Child Health 2009; Vol.33(2): 70-72